Observational and numerical analysis of the genesis of a mesoscale convective system - Nachamkin, Jason Edward, author (Colorado State University. Libraries, 1998)
A high resolution observational and numerical study was conducted on a mesoscale convective system (MCS) that developed in northeastern Colorado on 19 July 1993. Convection was followed from its origins in the Rockies west of Denver as it grew to near mesoscale convective complex (MCC) proportions over the plains. Five-minute surface data was collected from 48 mesonet stations over eastern Colorado, and six-minute dual Doppler data were collected from the CSU-CHILL and Mile High radars. The Regional Atmospheric Modeling System (RAMS) was then used to simulate this case. Initialization with variable topography, soil moisture, and atmospheric conditions facilitated the simulation of the inhomogeneous environment and its interactions with the MCS. Convection was explicitly resolved on the finest of four telescopically nested, moving grids. Storms developed consistently within the model without any artificial triggers such as warm bubbles or cold pools. Comparisons with the observations showed strong agreement down to the scale of the individual Doppler scans. The results show that convective position was deterministically focused by thermally driven solenoidal circulations and their interaction with a preexisting surface front. Away from the mountains, convection was fed by an intense low-level jet less than 200 km across. The jet formed over southeastern Colorado in a region of localized thermal contrasts on either side of the plains inversion. Interactions between convection and its surrounding environment existed in two modes. When the upward mass flux was of moderate strength, continuity was maintained by linear, low frequency gravity waves. Most of the wave energy propagated rearward from the convective line, even though strong upper tropospheric shear advected most of the condensate ahead of the line. Almost all of the environmental compensating motions propagated rearward with the waves, inducing upper tropospheric front-to-rear and mid tropospheric rear-to-front perturbations in their wake. Most of the subsidence heating was also restricted to the narrow zone of wave propagation. When the convective mass flux became intense near sunset, condensate, heat and momentum were advected directly into the upper troposphere in a nonlinear outflow. The oval-shaped cold cloud top was defined by the leading edge of the outflow, and unlike the gravity waves, gradients of heat and momentum only slowly dispersed. This suggests that intense MCSs and MCCs with well defined anvils are more likely to produce a balanced disturbance because proportionately less energy is lost to gravity waves.
February 5, 1998.
Also issued as author's dissertation (Ph.D.) -- Colorado State University, 1998.
Keywords: Mesometeorology; Convection (Meteorology); Cumulonimbus